Training small producers in Good Manufacturing Practices for the development of goat milk cheese - Ramón, Adriana Noemí (2018)
Training in Good Manufacturing Practices enhances quality during food processing. This paper evaluates GMP training aimed at improving the chemical, sensory and microbiological quality of goat milk cheese. We worked with 26 families that produce cheese as their main source of income. Semi-structured interviews and observation were conducted to select relevant topics. The manufacturing processes were compared and samples were analyzed before and after GMP training. We trained 80% of the producers. Before receiving training, they used to make cheese from raw milk in unhygienic conditions and with little equipment. The products obtained had bad sensory characteristics, cracks, eyes on the pasta, a high number of aerobic mesophilic bacteria and total coliforms. After training, the producers pasteurized the milk and standardized processing procedures, resulting in final products that contained higher protein and calcium content, suitable sensory characteristics, and a significant reduction in microorganisms, with total coliforms falling to ≤ 5.103 UFC/g. Therefore, this study shows that the manufacturing process and the chemical, sensory and microbiological parameters of goat milk cheese improved after GMP training.